Enterprise Resource Planning (ERP) and Management Controler : A Study of Manufacturing Industries in Banten - Muhammad Nawawi; Chandra Prasadhita; Luthfi Octavian (Jurnal Riset Akuntansi Terpadu, 2023)
The objectives of this study focus on the implementation of ERP and its impact on business and management controllers, and more specifically, it is necessary to present a new wave of information systems and to identify their impact on the relationship of management controllers with the entire management system within the company. The survey results were analyzed using Partial Least Squares - Structural Equation Modeling (PLS-SEM). PLS-SEM provides an estimate of the relationship between variables and constructions (measurement models) and between constructions (structural models). The system quality of the ERP affects the satisfaction of the management controller, then the quality of the ERP information also affects the satisfaction of the management controller. Furthermore, the user utility of the ERP system also directly affects the satisfaction of management controllers. Then, communication does not affect the satisfaction of the management controller because the better the system, the less intense communication will be. In conclusion, ERP convincingly transforms accounting practices within the company, by encouraging the formalization of operations, automation, and securing the recording of operations. ERP makes it possible to apply an event-driven accounting approach to practice. Data collection is ERP's main contribution to management controllers and leads to harmonization and improvement of budget information.Keywords: ERP, management controllers, communication and information systems